An Exploration of PPP Infrastructure Projects’ Risks in Supporting Sustainable Development and SDGs - Hassan, Jinan Kata'a; Mahjoob, Ahmed Mohammed Raoof (Salehan Institute of Higher Education, 2026)
Iraq has initiated “Iraq Vision 2030” as a participation in the global efforts to attain sustainable development and the United Nations’ Sustainable Development Goals (SGDs). The private sector engagement in infrastructure development was adopted as a national goal. However, no serious accomplishment has been made. Accordingly, this research was conducted to explore risk factors affecting sustainable development in public-private partnership (PPP) infrastructure projects. 116 risk factors were identified through literature review; for proper assessment, monitoring, controlling, and management, they were classified into two groups. The first group includes risk factors that may appear at a specific stage of the PPP project lifecycle. The second group includes risk factors that may appear at any time along the PPP project lifecycle. A field study has been implemented in two stages; the first stage is an open questionnaire and face-to-face interview with PPP experts to finalize and approve proposed risk lists. The second stage is a closed questionnaire; the mean value was used to rank and identify respondents’ agreement on rating the level of importance of these risk factors supported by nonparametric tests. Findings indicated that the critical-level risks form nearly two-thirds of the overall and first-group risks and more than two-thirds of the second-group risks. Financial and fiscal sustainability concerns form a serious challenge, as they came in at the top of the critical-level risk factors. Overall findings indicate the importance of legislating a PPP law that serves the achievement of “Iraq Vision 2030” national goals and the UN’s SDGs and provides a comprehensive framework that protects citizens’ rights, ensures their well-being, and supports sustainable development.